Hybrid WCMFO algorithm for the optimization of AWJ process parameters. Issue 1 (October 2020) - Tamilarasan, A; Rajmohan, T; Ashwinkumar, KG; Dinesh, B; Praveenkumar, M; Dinesh Reddy, R.; Surya Kiran, K V V; Elangumaran, R; Krishnamoorthi, S
Abstract: Selecting optimal and proper cutting parameters for achieving desired results in the AWJ process is a demanding task. Therefore, the main contribution of this work is to apply a new reliable hybrid WCMFO algorithm for process optimization in the AWJ process. Based on the box-behnken design technique, 17 experimental runs were conducted and quadratic model for surface roughness was developed to fit with experimental data. Then, the WCMFO algorithm is implemented in the consideration of surface roughness as a fitness function. The key advantage of this algorithm is that it does not accumulate to any local optima, and the existence of a hybrid algorithm allows it to store the best solutions available so far. The predicted optimal settings were verified through confirmatory experiments, and the results validated.